If your monster won't go to bed - Vega, Denise (Alfred A. Knopf, 2017)
A handbook for youngsters that includes such instructions as "pour your monster a nice big glass of healthy, crunchy, oozy bug juice slimed with ooey-gooey snail trails to calm him."